Study of insulin resistance as an inflammatory marker for ischemic stroke severity among non-diabetics - Nawaz, Mohammed M.; Sundaramurthy, Harsha; S. C., Nemichandra; Paneyala, Shasthara (International Journal of Research in Medical Sciences, 2023)
Background: Insulin resistance (IR) is emerging as an important modifiable risk factor causing acute ischemic stroke. The purpose of the study was to evaluate insulin resistance among patients of acute ischemic stroke, in non-diabetic patients, and to correlate insulin resistance with the severity of acute ischemic stroke, and to observe its association with traditional risk factors. Methods: It was a prospective study conducted at JSS Medical College, Mysore, India from September 2021 to December 2022. Patients who presented with the history of stroke, who were non-diabetics and aged >18 years were included with informed consent. Ischemic stroke was diagnosed with clinical findings and by neuroimaging. Stroke severity was assessed by NIHSS score. Homeostasis model assessment (HOMA) was used to estimate insulin resistance and the levels were studied in relation to the stroke severity. Results: A total of 127 non-diabetic ischemic stroke patients were enrolled in the study. Hyperinsulinemia, i.e. serum insulin >9 μU/mL, was observed in 44 (34.64%) patients. IR with HOMA-IR ≥2.5 was noted in 39 (30.7%) patients. NIHSS score in severity (group III) was strongly associated with serum insulin >9 μU/mL (62.1%) (P = 0.001) and HOMA-IR ≥2.5 (62.1%) (P<0.0001). Conclusions: Screening for insulin resistance in nondiabetic patients with ischemic stroke may identify those who are at higher risk for poor outcomes, allowing for early intervention and closer monitoring. Also, interventions to reduce insulin resistance, such as lifestyle modifications or medications, may be beneficial in improving stroke outcomes.